Bagaimana Pengaruh Scarcity Promotion Terhadap Online Impulse Purchasing - Gracia Tiffany Sutrisno; Leonny Surya Santoso Santoso; Crisca Nathania Tandjung (Jurnal Ilmiah Psikologi MIND SET, 2022)
Change during pandemic has an impact on economic activities where the community has to turn to the online buying and selling system. Various marketing methods are carried out by several e-commerce companies, one of them by giving various promos. This study aimed to know the effect of the limited time scarcity (LTS) factor and the limit quantity scarcity (LQS) factor on online impulsive purchases. This study used factorial experimental 2x2. We obtained quantitative data from scales that we used and qualitative data from an open questionnaire. The Limited Scarcity Manipulation measuring instrument was used with a total of 47 female respondents, ages 18-34 years who were domiciled in Surabaya or Bali. Based on the open questionnaire, most of the participants have knowledge about Somethinc. product. The results of this study indicate that limited time scarcity (LTS) and limited quantity scarcity (LQS) have not significantly predicted impulsive purchasing. Impulsive purchasing was mostly done by the LTS only group and the LQS only group.